Deadly deals - Michaels, Fern (New York : Zebra Books, 2009)
After spending Thanksgiving with their loved ones on Big Pine Mountain, the ladies of the Sisterhood prepare to assist attorney Lizzie Fox in breaking up an illegal baby selling ring.
Keywords: Adoptive parents -- Fiction; Suspense fiction